Exploring sustainable management by using green nano-silver to combat three post-harvest pathogenic fungi in crops - Sudhir S. Shende; Aniket K. Gade; Tatiana M. Minkina; Pramod U. Ingle; Vishnu D. Rajput; Svetlana N. Sushkova; Saglara S. Mandzhieva; Mahendra Rai; Ming H. Wong (Discover Nano, 2024)
Abstract Global crop protection and food security have become critical issues to achieve the ‘Zero Hunger’ goal in recent years, as significant crop damage is primarily caused by biotic factors. Applying nanoparticles in agriculture could enhance crop yield. Nano-silver, or AgNPs, have colossal importance in many fields like biomedical, agriculture, and the environment due to their antimicrobial potential. In this context, nano-silver was fabricated by Citrus medica L. (Cm) fruit juice, detected visually and by UV–Vis spectrophotometric analysis. Further, AgNPs were characterized by advanced techniques. UV–Vis spectroscopic analysis revealed absorbance spectra at around 487 nm. The zeta potential measurement value was noted as -23.7 mV. Spectral analysis by FT-IR proved the capping of the acidic groups. In contrast, the XRD analysis showed the Miller indices like the face-centered cubic (fcc) crystalline structure. NTA revealed a mean size of 35 nm for nano-silver with a 2.4 × 108 particles mL−1 concentration. TEM analysis demonstrated spherical Cm-AgNPs with 20–30 nm sizes. The focus of this research was to evaluate the antifungal activity of biogenic AgNPs against post-harvest pathogenic fungi, including Aspergillus niger, A. flavus, and Alternaria alternata. The Cm-AgNPs showed significant antifungal activity in the order of A. niger > A. flavus > A. alternata. The biogenic Cm-AgNPs can be used for the inhibition of toxigenic fungi.